Staphylococcus spp. Isolated from Spiders and their Antimicrobial Sensitivity against Essential Oils - Miroslava Kačániová; Mariia Fedoriak; Margarita Terentjeva; Maciej Kluz; Pawel Hanus; Czeslaw Puchalski (Scientific Papers Animal Science and Biotechnologies, 2023)
Research on insects and their bacterial communities provides valuable information on potential interaction between the host and their symbiotic bacteria. The aim of the present study was to evaluate antimicrobial activity of essential oils against Staphylococcus spp. isolated from spiders. Spiders samples were investigated microbiologically and Staphylococcus isolates were confirmed with MALDI TOF MS Biotyper. Antimicrobial activity of Satureja hortensis L., Pimpinella anisum L., Rosmarinus officinalis L., Salvia officinalis L. and Ocimum basilicum L. essential oils was detected.  Altogether five Staphylococcus species were identified: S. capitis, S. epidermidis, S. haemolyticus, S. warneri and S. xylosus. All bacterial strains were resistant of ciprofloxacin, levofloxacin, amikacin and gentamicin. S. haemoliticus was the most resistant against essential oils of Rosmarinus officinalis L., Salvia officinalis L. S. warneri and S. xylosus were the most sensitive against antimicrobial action of the applied EOs.